Unmasking Cleckley's psychopath: assessing historical case studies - DeShong, Hilary L.; Helle, Ashley C.; Mullins-Sweatt, Stephanie N. (Personality and mental health, 2016)
The current study investigated original case descriptions of psychopathy (Cleckley, 1941) in relation to current conceptualizations and general personality traits. Attorneys, forensic psychologists and clinical faculty members completed ratings of psychopathy and personality after reading vignettes based on Cleckley's descriptions of a psychopath. The results suggest that professionals' ratings are consistent with current conceptualizations of psychopathy. Furthermore, the five‐factor model (FFM) personality traits of the vignettes aligned with the current literature on the FFM and psychopathy (i.e. low neuroticism, conscientiousness and agreeableness). The results further supported that a general trait model, like the FFM, may be well suited to describe the underlying personality traits of psychopathy. Gender differences were also examined.